Faktor Penyebab Terjadinya Duplikasi Penomoran Rekam Medis di Fasilitas Pelayanan Kesehatan - Feby Erawantini; Tamami Alifia Annisa; Ervina Rachmawati; Demiawan Rachmatta Putro Mudiono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Medical record files that have not been combined with previous files will determine information on services provided to patients which results in patient data being unstructured, it is difficult for doctors to provide diagnoses and therapy to patients, this is related to service quality. So a study is needed to review the factors that cause duplication of medical record numbering based on the Man, Money, Method, Machine, and Materials factors. This literature review uses the Google Scholar database, the Garuda portal, and Crossreff. Obtained 1022 articles which were then selected 16 articles. The results of the review show that the man element is the lack of accuracy and responsibility of officers, the minimum number of officers with medical record education, and the lack of training and seminars for officers; the element of money is a limited source of funds for, as well as an increase in the budget due to the increased use of supporting materials; the method element is the lack of SOP implementation; machine element is a system that still often errors; the material element is that infrastructure is available, but not used properly, patients still often do not carry MNH.Keywords: medical record; duplication; management ABSTRAK Berkas rekam medis yang belum digabungkan dengan berkas sebelumnya akan memutuskan informasi pada pelayanan yang diberikan kepada pasien yang mengakibatkan data pasien menjadi tidak terstruktur, sulit bagi dokter dalam memberikan diagnosa dan terapi pada pasien, hal ini terkait dengan mutu pelayanan. Maka diperlukan studi untuk mereview faktor penyebab terjadinya duplikasi penomoran rekam medis berdasarkan faktor Man, Money, Method, Machine, dan Materials. Literature review ini menggunakan database Google Scholar, portal Garuda, dan Crossreff. Didapatkan 1022 artikel yang selanjutnya terpilih 16 artikel. Hasil review menunjukkan bahwa unsur man adalah kurangnya ketelitian dan tanggung jawab petugas, minimnya petugas berpendidikan perekam medis, serta kurangnya pelatihan dan seminar bagi petugas; unsur money adalah sumber dana yang terbatas untuk, serta naiknya anggaran karena bertambahnya penggunaan material pendukung; unsur method adalah kurangnya implementasi SOP; unsur machine adalah sistem yang masih sering error; unsur material adalah sarana prasarana sudah tersedia, namun tidak digunakan dengan baik, pasien masih sering tidak membawa KIB.Kata kunci: rekam medis; duplikasi; manajemen